2009
DOI: 10.1242/jcs.040121
|View full text |Cite
|
Sign up to set email alerts
|

TC10 controls human myofibril organization and is activated by the sarcomeric RhoGEF obscurin

Abstract: The contractile activity of striated muscle depends on myofibrils that are highly ordered macromolecular complexes. The protein components of myofibrils are well characterized, but it remains largely unclear how signaling at the molecular level within the sarcomere and the control of assembly are coordinated. We show that the Rho GTPase TC10 appears during differentiation of human primary skeletal myoblasts and it is active in differentiated myotubes. We identify obscurin, a sarcomere-associated protein, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
0
27
2
Order By: Relevance
“…Recent studies have identified RhoA (Ford et al, 2008) and TC10, also known as RhoQ (Coisy-Quivy et al, 2009), as targets for activation by the obscurin RhoGEF domain. Demonstration that the RhoGEF domain of Unc-89, the invertebrate orthologue of obscurin, is capable of activating Rho1, the invertebrate orthologue of RhoA (Qadota et al, 2008) further supports RhoA as a target of obscurin-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified RhoA (Ford et al, 2008) and TC10, also known as RhoQ (Coisy-Quivy et al, 2009), as targets for activation by the obscurin RhoGEF domain. Demonstration that the RhoGEF domain of Unc-89, the invertebrate orthologue of obscurin, is capable of activating Rho1, the invertebrate orthologue of RhoA (Qadota et al, 2008) further supports RhoA as a target of obscurin-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to binding and activating RhoA, the obscurin RhoGEF motif interacts with and activates TC10 that also belongs to the Rho family of GTPases (104). TC10 appears after the fusion of myoblasts, and its expression is maintained in differentiating and mature myotubes (103).…”
Section: Obscurinmentioning
confidence: 99%
“…TC10 appears after the fusion of myoblasts, and its expression is maintained in differentiating and mature myotubes (103). Downregulation or overexpression of a dominant-negative form of TC10 in human myotubes demonstrated that it is essential for myofibril assembly, indicating that the interaction of obscurin RhoGEF and TC10 may play key roles in sarcomerogenesis (104). …”
Section: Obscurinmentioning
confidence: 99%
“…TC10, a small GTPase not previously thought to influence the biology of striated muscle, is expressed in skeletal myotubes and is activated by obscurin's Rho-GEF domain. This is likely to play a role in later stages of differentiation, as inhibition of TC10 activity blocks myofibrillogenesis (53). The ability of obscurin to activate small GTPases in muscle, and the factors that influence this activation, are likely to play a wide range of important roles in the plasticity of muscle tissue, in particular during development, as well as in its response to injury or during atrophy or hypertrophy.…”
Section: Obscurinmentioning
confidence: 99%